Renegotiating police legitimacy through amateur video and social media: lessons from the police excessive force at the 2013 Sydney Gay and Lesbian Mardi Gras parade. Issue 3 (3rd July 2019) - Ellis, Justin
ABSTRACT: This article examines the impact of digital media technologies on police-lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ) community relations in Sydney through a viral video of police excessive force filmed after the 2013 Sydney Gay and Lesbian Mardi Gras parade. Critical media analysis, and 15 in-depth interviews with police and non-police respondents directly affected by the video, make an in-depth, qualitative contribution to legitimacy and procedural justice studies on the impact of digital technologies on LGBTIQ community trust in police. The findings emphasise the capacity of amateur video of police excessive force publicised directly through social media to pressure the police to account, to catalyse LGBTIQ community responses and to negotiate through online fora legitimate boundaries of police practice. Exposure through social media can pressure the police to justify police transgression in real time; a form of 'dynamic' legitimacy requiring continuous and detailed justification of police practice that can exhaust standard police responses through a potentially infinite claim-response dialogue. Despite revision of policing practices at Mardi Gras since 2013, ongoing discrepancies between police understanding and public perceptions of a range of police tactics, including use of force, emphasise the continued importance of dialogue between police and LGBTIQ communities.